PENGEMBANGAN MEDIA GAME EDUKASI BERBASIS WEB WORDWALL PADA MATERI BALOK DAN KUBUS KELAS IV SD DALAM KURIKULUM MERDEKA - Salshabila Salshabila; Moh Rosyid Mahmudi; Sonia Yulia Friska (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to develop an educational game learning media based on the Wordwall web to arouse students' enthusiasm in participating in the teaching and learning process or when evaluating learning in mathematics content. The research method used is (research and development) or the ADDIE development method which consists of 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. The types of data used are qualitative and quantitative. Data collection instruments in the form of validation sheets, practicality, and effectiveness. For data collection techniques used are interview techniques, observation, questionnaires and documentation. Analysis of the data used is the analysis of products developed using analysis of media validity, practicality and effectiveness of the media. Based on the development that has been carried out, the validation results of the Wordwall web-based educational game media are obtained. This validation shows that the results obtained with a percentage of 92% are in a very valid category. Practicality was assessed from the teacher's response questionnaire and the fourth grade student's response questionnaire to the Wordwall web-based educational game media as a learning media for mathematics on blocks and cubes, which obtained a percentage of 87% in the very practical category. Effectiveness is assessed from student learning outcomes. The learning outcomes of fourth grade students at SD Negeri 01 Durian Gadang who completed a percentage of 86% in the very effective category.